Alternative Fikih in Sharia Economics (An Offer of Takhayur Fikih) - Nafi, Muhammad; Ulayya, Muhammad Sholah; Mahmudin, Mahmudin; Bahamisy, Muhammad Hamid Muhammad; Alrumayh, Safa Husayn (Waralaba : Journal Of Economics and Business, 2025)
The study of muamalah fiqh has an important role in the development of sharia economics, especially in determining transaction rules that are in accordance with Islamic principles. This study discusses the concept of alternative fiqh in sharia economics through the takhayyur fiqh approach, namely the selection of legal opinions that are more relevant and contextual in the dynamics of the modern economy. This study highlights how Islamic law, especially in muamalah, is dynamic and able to adapt to social, economic, and technological changes. In this study, the method used is library research with an analytical approach to various classical and contemporary fiqh sources. The results of the study show that the application of fiqh that is more flexible and in accordance with the realities of the modern economy can increase the competitiveness of sharia financial institutions and provide solutions to regulatory challenges. In addition, this study reveals that the takhayyur fiqh approach can be an alternative in responding to social change without ignoring the basic principles of sharia. Thus, a reactualization of Islamic law in sharia economics is needed to bridge the provisions of classical fiqh with the needs of the contemporary economy.